A quantitative PCR assay for the detection of low amounts of malignant cells in multiple myeloma - Cremer, Friedrich Walter; Kiel, Katja; Wallmeier, M.; Goldschmidt, Hartmut; Moos, Marion (Annals of oncology, 1997)
Background - High-dose chemotherapy (HDT) with autografting of hematopoietic stem cells induces up to 50% of complete remissions in patients with multiple myeloma. Cases of molecular remissions have been reported. However, qualitative assays determine only the absence or presence of a monoclonal population depending on their sensitivity. Therefore reliable and sensitive methods to quantitate tumor loads are neccessary. - Materials and methods - We have established a quantitative PCR assay (qPCR) with allele-specific primers complementary to hypervariable CDR3 regions. Sample DNA was serially diluted in 0.5 log steps and amplified in 10 replicates. PCR results were analysed by likelihood maximization and x2 minimization to calculate the tumor load. - Results - Three approaches were taken to validate the qPCR. 1) Single copies of the CDR3 region of U266 cells could be detected. 2) Analysis of a bone marrow sample by FACS for CD 38++ and k/λ restricted plasma cells and by qPCR yielded results of 1.4 and 2.5% respectively. 3) qPCR results with plasmids carrying CDR3 regions simulating different tumor loads diverged by no more than a factor of 1.6 from the expected values. - Conclusions - We consider the qPCR to be an accurate method for assessing samples with low amounts of malignant cells.
Elektronische Reproduktion der Druck-Ausgabe 8. Januar 2020
Gesehen am 24.04.2025